INFORMATION COMMUNICATION TECHNOLOGY (ICT) AND MEDIA EDUCATION: IN HISTORICAL PERSPECTIVE - Kabir Mohammed; Binta Muhammad Yarinchi (European Scientific Journal, ESJ, 2013)
The role and impact of information and communication technology on modern academic world in general cannot be left unstudied. It is against this background the study argues that if it had not been for the art of writing and printing founded as a result of technological revolution there would have been no full learning as currently and evidently found taking right shape. In view of this, it should therefore be borne in mind that industrialization is fundamentally the backbone of our contemporary progress and achievements and the positive impact claims to have on our academic life cannot be overemphasized. The study examines the concept of ‘media technology’, history of the world of information technology, relevance and significance to teaching and learning processes, and has further explored the role played by (ICT) in revolutionizing academic activities. Finally, solutions to the problems confronting teaching profession, learning and the use of computer in Nigerian area, in particular have been presented as way forward.